Novel Roles of Follistatin/Myostatin in Transforming Growth Factor-β Signaling and Adipose Browning: Potential for Therapeutic Intervention in Obesity Related Metabolic Disorders - Pervin, Shehla; Reddy, Srinivasa T.; Singh, Rajan (Frontiers in Endocrinology, 2021)
Obesity is a global health problem and a major risk factor for several metabolic conditions including dyslipidemia, diabetes, insulin resistance and cardiovascular diseases. Obesity develops from chronic imbalance between energy intake and energy expenditure. Stimulation of cellular energy burning process has the potential to dissipate excess calories in the form of heat via the activation of uncoupling protein-1 (UCP1) in white and brown adipose tissues. Recent studies have shown that activation of transforming growth factor-β (TGF-β) signaling pathway significantly contributes to the development of obesity, and blockade or inhibition is reported to protect from obesity by promoting white adipose browning and increasing mitochondrial biogenesis. Identification of novel compounds that activate beige/brown adipose characteristics to burn surplus calories and reduce excess storage of fat are actively sought in the fight against obesity. In this review, we present recent developments in our understanding of key modulators of TGF-β signaling pathways including follistatin (FST) and myostatin (MST) in regulating adipose browning and brown adipose mass and activity. While MST is a key ligand for TGF-β family, FST can bind and regulate biological activity of several TGF-β superfamily members including activins, bone morphogenic proteins (BMP) and inhibins. Here, we review the literature supporting the critical roles for FST, MST and other proteins in modulating TGF-β signaling to influence beige and brown adipose characteristics. We further review the potential therapeutic utility of FST for the treatment of obesity and related metabolic disorders.